ANALISIS KEDISIPLINAN KARYAWAN PT. TOTAL JAYA INTERNATIONAL - WILI CHANDRA; HENNY SUHENNY; DIDING KUSNADY; TASIK UTAMA; WONG PONG HAN (JURNAL ILMIAH KOHESI, 2019)
In this study, researchers conducted research on employee discipline at PT. Total Jaya International Lubuk Pakam, with theresearch title "Employee Discipline Analysis at PT. Total Jaya International Lubuk Pakam ". Researchers want to know howthe discipline of employees at PT. Total Jaya International Lubuk Pakam. Researchers used descriptive qualitative methodsand used data collection techniques namely structured interviews, Miles and Huberman model data analysis methodsconsisting of data reduction, data presentation and drawing conclusions. The results of this study indicate that PT. Total JayaInternational Lubuk Pakam has established rules. Among them are hours of entry / exit work, hours of rest and workdiscipline in using office equipment. The conclusion of this research is employee discipline at PT. Total Jaya InternationalLubuk Pakam is still lacking and needs to be improved in time discipline and work discipline.